Bioinspired building materials—lessons from nature - Sandak, Anna; Butina Ogorelec, Karen (Frontiers in Materials, 2023)
Systems found in nature are a valuable source of inspiration for several applications. Scientists and researchers from different fields (structural engineering, robotics, medicine, materials science) use the concepts of biomimicking, biomimetics, and bioinspiration. More recently the possibility to benefit from solutions developed by nature has become of interest for sustainable architecture. Living organisms use smart, optimised, and elegant solutions to survive, thanks to continuous selection and mutation processes. For over 460 million years plants have been evolving in a constantly changing environment and have become well-adapted to different climatic conditions. Faced with several challenges (water loss, extreme temperatures, UV radiation, etc.) plants, for example developed tissues with barrier properties. Furthermore, due to their immobility, plants are excellent biological materials for detecting climate phenomena. While animals, being mobile, developed other creative survival strategies through a long evolutionary process. Being exposed to various environments, they not only developed multifunctional surfaces, but also movements and a broad portfolio of sensing methods that increased their survival efficiency.Comprehensive analysis and evaluation of the adaptation strategies of plants (both static strategies and dynamic mechanisms) and animals to their environment in different climate zones are indispensable for transferring concepts from biology to architecture. Consequently, specific adaptation solutions might be implemented in new materials that will be used for building envelopes erected in the same climatic zones. Integrating length scales and mixing biological, chemical, and physical concepts for tailoring the properties of materials during preparation should allow for better designing of future smart materials. The process should lead to the development of active biomaterials that perform as interfaces between outdoor conditions and internal comfort. In that they should be able to regulate humidity, temperature, CO2, and light as well as capture and filter pollutants; in addition, they should have self-assembling, self-cleaning, grafting, and self-healing properties. This contribution provides an analysis of several examples that represent the adaptation of organisms to various environments and are presented with the aim to inspire future researchers in the development of new building materials.